Once daily Asacol. (13th March 2011) - Hawthorne, A B; Stenson, R; Gillespie, D; Swarbrick, E T; Dhar, A; Kapur, K C; Hood, K; Probert, C S
Abstract : Introduction: Mesalazine has traditionally been administered in divided doses, but there is emerging evidence that once daily dosing is no less effective and may improve treatment adherence. Methods: The Colitis Once Daily Asacol® (CODA) study was designed to assess the efficacy and safety of once daily dosing with Asacol® 2.4 g given as 3 × 800 mg tablets (OD) in comparison with three times daily dosing (one 800 mg tablet three times daily) (TDS). Adult UC patients taking mesalazine or sulphasalazine in remission for >4 weeks and <2 years were randomised (investigator-blind) to OD or TDS dosing. The primary end-point was the difference between groups in relapse rates over one year. Relapse was defined as typical symptoms of relapse with a Baron sigmoidoscopy score of 2 or 3. With estimated relapse rate of 20–30%, and a meaningful difference of 10% between groups, 250 patients were required to demonstrate non-inferiority with one-sided α of 5% and 1-β of 80%. Non-inferiority would be concluded if the upper limit of the 95% confidence interval (CI) for the difference between treatments was <10% for both per protocol (PP) and intention to treat (ITT) population. (For ITT analysis, missing data was imputed as relapse.) Results: 213 patients were recruited in 32 UK centres. Groups were well matched. There was no difference in adverse events between OD and TDS groups. Primary analysis confirmed non-inferiority of once-daily dosing. In a secondary analysis, (table 1 ) both ITT and per protocol (PP) populations demonstrated superiority of OD versus TDS dosing which was statistically significant. A multivariable analysis of baseline factors predicting relapse will be presented. Self-reported adherence at 12 months or relapse was >90% in 97% of patients (OD group) and 85% (TDS group). When asked how easy it was to remember to take tablets, it was reported to be very or fairly easy in 98% (OD group) versus 73% (TDS group). Conclusion: Once daily dosing with Asacol ™ 2.4 g is as safe and effective as three times daily dosing, and secondary analysis confirmed significantly reduced relapse rates. The benefit was, however, clinically borderline and may relate to ease of adherence.